ANALYSIS OF RESERVOIR GEOMECHANICS AND THE EFFECT ON THE RECENT STRAIN CONDITION IN SOUTH SUMATERA BASIN - ZHAKY YOLANDY - NIM: 22015020, BILLY
South Sumatera Basin is located in the southern part of Sumatera Island which is bordered by Barisan Mountain Range at the western part, Tigapuluh Mountain Range at the northwest, and Bangka Island in the eastern part. Geologically, South Sumatera Basin is divided into three Sub-basin such as Jambi Sub-basin, Central Palembang Sub-basin, and South Palembang Sub-basin. The Basin is categorized as tertiary back arc basin and formed as a result of interaction between Sunda Shelf and Indian Ocean Crust. With the occurrence of such interactions, accommodation space is created for sedimentation to occur. The sediment is contributed for hydrocarbon production in this basin. To increase production and to decrease ineffective time during drilling, comprehensive study of the Sumatra Basin needs to be done since the basin has contributed significantly to Indonesian oil production and there are some great potential in its non-conventional oil and gas play. Reservoir geomechanics can help in this endeavor. Broadly speaking, this method is a method that calculates and predicts the value of stress that lies beneath the surface (vertical stress, horizontal stress, pore pressure, and rock strength). In addition to the value of stress, the principle stress direction is also the object of this part of study. Modulus elasticity analysis using wireline log data shows the existence of a pattern which indicate the smaller value of poissonÃ‚Â’s ratio (v) and bigger value of modulus young (E) along with depth. This data suggest that rock will be relative harder with depth. However, there are some rock formation intervals that do not follow this pattern caused by the fact that there is difference in the material components and the rock type itself. Image log data can be used in determining the direction of principal stress direction of an area by interpreting the occurrence of induced tensile fractures and borehole breakout. The direction of induced tensile fracture represents the direction of SHmax and the direction of the borehole breakout presence represent the direction of Shmin. Interpretation of image log indicating the direction of maximum horizontal stress (SHmax) is relatively northeast-southwest in Jambi Sub-basin and the eastern part of Central Palembang Sub-basin (N300E-N400E). Data form world stress map on the Central Palembang Sub-basin and South Palembang Sub-basin show that the direction of principal stress is consistent with the interpretation of image log data which is northeast-southwest (N300E-N600E). Observation on anticline patterns that appear on the horizon interpretation data suggest that antclines tend to directed on northwest-southeast (N1000E-N1500E). The anticline direction that is observed tends to be perpendicular to the direction of the observed stress so it can be concluded that the existing stress that is monitored in this basin is controlling the pattern of anticline(strain) formed. Interpretation on the image log and its combination with the wireline log can be used to determine the magnitude of the in-situ stress. Vertical stress in the study area had a gradient range value of between 0.87psi/ft to 1.02psi/ft.The value of LOT data (Leakf Off Test) that is used in determination of shmin gives linear regression equation in the form of Shmin (psi)=(Kedalaman (m)-29,965)/0,3647 for Jambi Subbasin, Shmin(psi)=(Kedalaman (m)-41,363)/0.3469 for Central Palembang Subbasin, and Shmin(psi)=(Kedalaman(m)-20,083)/0,3996 for South Palembang Subbasin. Shmin gradient in the study area ranged from 0,75psi/ft to 0,85psi/ft. Indication of induced borehole breakout and induced tensile fracture can be used to calculate lower bound value of SHmax. The width of the induced borehole breakout fracture used in the calculation is between 100-500 with peak data at 200-300. The calculation of the in-situ stress in this basin indicates that the stress regime which generally works on the study area is strike-slip fault regime. However there is an area in the Central Palembang Sub-Basin that shows the area is in a strike-slip / reverse area which shows the same value between Shmin and Sv. This phenomenon is caused by the high pore pressure on the area and the latter referred to as the stress coupling causing the increase for both horizontal stress.